The conceptualization of body image: a qualitative exploration in overweight adolescents - Sidek, Suriati (IIUM Press, International Islamic University Malaysia, 2017)
Overweight adolescents appear to be at particular risk of developing body dissatisfaction because their body image and shape deviate further from the cultural standard of body ideal. Previous studies suggested that body image can be studied in four different domains that include perceptua l, cognitive, affective and behavioral. Therefore, this phenomenological study aims to explore the conceptualization of body image from the perspective of overweight adolescents. Thirty-three overweight adolescents aged 13 to 17 from an urban setting in Selangor were interviewed. The thematic analysis identified that body image is conceptualised through perceptual, affective, cognitive and behavioral domains. Overweight adolescents perceived body attributes as more important than other physical characteristics. They described their body image as it is based on the appearance comments and criticism that they received from social interactions with peers and parents. Most of them wanted to be thin for social acceptance. They believed that they may have difficulties in looking for a partner and susceptible to diseases based on their observation of other people and through available information from significant others and the media. They experienced weight-related teasing, peer rejection and negative stereotyping in daily encounters. These perceptions, beliefs, and personal experiences and observation may lead to body dissatisfaction. Although most participants are dissatisfied with their current body image, few however were having positive views of their bodies by highlighting the self-enhancement mechanisms. All overweight adolescents interviewed in this study, including those with a positive view of their body image wanted to reduce weight. This study has given a significant contribution to the current knowledge with respect to the methodological approach and the conceptual framework of body image in the form of a newly developed framework. The proposed framework may explain the conceptualization of body image among overweight adolescents.